EKSISTENSI HUKUM ADAT SEBAGAI ASSET NAGARI DI PROPINSI SUMATERA BARAT PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 35/PUU-X/2012 - Yarsina, Nova (Ensiklopedia Sosial Review, 2019)
MK Decision No. 35 / PUU-X / 2012 concerning testing Law No. 41 of 1999 concerning Forestry, brought a breath of fresh air to indigenous and tribal peoples, in which in its decision the Constitutional Court has emphasized the existence of customary forests as private forests and is no longer part of state forests as well as serious recognition of the existence of indigenous and tribal peoples. Where in the Constitutional Court's decision No. 35 / PUU-X / 2012 regarding the review of Law Number 41 of 1999 concerning Forestry, the judge tried to provide an ideal decision based on the legal objectives and has been reflected in the ruling elements of justice (Gerechtigkeit), legal certainty (Rechtssicherheit) and expediency (Zweckmassigkeit). These three elements can be found when not only in the Constitutional Court's decision, but in an interrelated legal system. Which, the legal system does not only refer to the rules (codes of rules) and regulations (regulations), but includes a broad field, including the structure, institutions and processes (procedures) that fill it and related to the law that lives in society (living law ) and legal culture (legal structure). As the theory put forward by Laurence M. Friedman that the elements of the legal system consist of legal structure, legal substance and legal culture. Researchers hope that in the future indigenous and tribal peoples can be more affirmed their rights regarding their forest land rights, and regional governments are more responsive to the needs of indigenous and tribal peoples.